2002
DOI: 10.1016/s0141-3910(02)00003-4
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene/graphite nanocomposites: effect on thermal stability

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 22 publications
4
43
0
Order By: Relevance
“…PEI (polyethyleneimine) is also used as hydrophobic segments, which is known to improve the stability of SiC and CNT in aqueous media by PEI [38]. Uhl and Wilkie [24] and Min et al [25] have reported that parallel hexagonal networks of carbon atoms in graphite sheet are held together at certain spacing by weak van der Waals forces. During sonication process, (20 kHz and 20 W) the individual layer of hexagonal network of carbon atoms in graphite particles are detached eas- ily due to weak van der Waals forces which leads to reduction in particle size from 250 to less than 50 µm which was confirmed in FESEM micrographs (Figure 2a-2b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEI (polyethyleneimine) is also used as hydrophobic segments, which is known to improve the stability of SiC and CNT in aqueous media by PEI [38]. Uhl and Wilkie [24] and Min et al [25] have reported that parallel hexagonal networks of carbon atoms in graphite sheet are held together at certain spacing by weak van der Waals forces. During sonication process, (20 kHz and 20 W) the individual layer of hexagonal network of carbon atoms in graphite particles are detached eas- ily due to weak van der Waals forces which leads to reduction in particle size from 250 to less than 50 µm which was confirmed in FESEM micrographs (Figure 2a-2b).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that layered materials may be beneficial for the enhancement of polymer properties. Once clay materials are dispersed uniformly in a polymer matrix, the properties can be largely enhanced [24,25]. Graphite as a layered structured material demonstrates enhancement of properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphite is naturally abundant allotrope of carbon which is made almost entirely of carbon layers. In the layers, carbon atoms are bounded by Van der Waals forces and the absolute separation of graphite layers is difficult due to higher crystal lattice energy [4,5]. Various methods have been explored for the preparation of hybrids with optimal physical properties and homogeneous dispersion of graphite particles in polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Clay/polymer nanocomposites often have properties that are dramatically different from those of the polymer alone with unique improvements in mechanical strength [4], thermal stability [5], flammability [6] and gas permeability [7]. The compatibility of the clay between the polymer and the clay is crucial for the formation of well-dispersed nanocomposites [6].…”
Section: Introductionmentioning
confidence: 99%